TREATMENT OF TIC HYPERKINESIS IN CHILDREN - Uzokova Musavvara Хisravovna; Norkulov Ural Tulaboevich; Zaripov Javohir; Dilshod Ibrohimov; Kasimov Arslanbek Atabayevich; Mamurova Mavludakhon Mirkhamzayevna (Western European Studies, 2024)
Tics in children are sudden repetitive movements resulting from involuntary contractions of various muscle groups. They are manifested by compulsive mimic, motor and vocal actions: blinking, squinting, twitching of the nose, mouth, shoulders, fingers, hands, turning the head, squatting, jumping up, shaking, coughing, noisy breathing, pronunciation of sounds, words. Comprehensive diagnosis includes examination of a neurologist, consultation with a psychiatrist, psychodiagnostic examination. Treatment is based on observance of a daily regimen, psychotherapy, psychocorrection, and medication
Keywords: infantile cerebral palsy; speech disorders; hyperkineses